Phylogenetic relationships among reindeer lichens of North America. (3rd May 2016) - ATHUKORALA, Sarangi N. P.; PINO-BODAS, Raquel; STENROOS, Soili; AHTI, Teuvo; PIERCEY-NORMORE, Michele D.
Abstract: Cladonia is one of the largest lichen-forming ascomycete genera. It was formerly divided into ten sections, three of which, Crustaceae ( Cladina ), Tenues, and Impexae, are called the reindeer lichens. While previous studies have elucidated the relationships between species and sections, they often examined only one or a few specimens of each species in the analysis. This study examined the monophyly of selected members of sections Crustaceae, Tenues, and Impexae and their relationships in the genus Cladonia using the internal transcribed spacer region of the nuclear ribosomal DNA (ITS rDNA) and the mitochondrial small subunit gene of the mitochondrial ribosomal DNA (mtSSU). The phylogenetic tree contained four clades, two representing species in section Impexae, one representing species that belong to sections Crustaceae and Tenues, and one clade with C. arbuscula and related species. Five of 22 species, C. pycnoclada, C. stellaris, C. evansii, C. ciliata and C. subtenuis, showed monophyly in the phylogenetic tree; some of these 5 species have been shown previously to be monophyletic. The thallus branching pattern was interpreted as an important heritable character using the mtSSU network. Three duplets of paraphyletic species were further examined using ITS rDNA haplotype networks and AMOVA analysis. The results for the species duplets showed some mixing of haplotypes but the AMOVA analysis provided support for species separation within the duplets. While the evidence supports distinct species, further study is needed to conclusively show separate species in these duplets.